Huffman Algorithm for Secured Data Transmission - Kanniga, E. (International Journal of Psychosocial Rehabilitation, 2019)
Neither watermarking nor compression can alone make the data transmission completely secure. Hence the new technique is been proposed in order to achieve secure transmission of data by making combine use of image watermarking using DCT technique and then applying image compression technique using improved adaptive Huffman algorithm to it